Variação no preenchimento da posição determinante antes de possessivos pré-nominais: padrões dialetais e contatos - Silva, José Manoel Siqueira da (2020)
The filling of the determiner position before pre-nominal possessives varies in Brazilian Portuguese, such as "eu vi o seu irmão ontem" and "eu vi seu irmão ontem". Researches with oral data show that this phenomenon is a dialectal marker: speakers from the Northeast region of Brazil non-fill more than those from the South and Southeast region (SILVA, 1982; 1998a; 1998b; CALLOU; SILVA, 1997; CAMPOS JR., 2011; GUEDES, 2019; PEREIRA, 2017; SEDRINS et al.; 2019; SIQUEIRA, 2020b), besides that, speakers of a dialect, inserted in a new community, adopt the linguistic behavior of the new social group regarding this variation (GUEDES, 2019). As a result of the expansion policies in higher education in the last decade in Brazil, the Federal University of Sergipe (UFS), Campus Prof. José Aloísio de Campos, São Cristóvão, SE, receives students from different places that interact with each other and have contact with different dialects, being able to adopt new linguistic forms in their repertoire or spread forms from their original community. In this work, we describe the uses of the not filling of the determiner position before pre-nominal possessives in the speech of UFS students, taking into account their region of origin, analyzed here Alagoas, Bahia and Sergipe, and their integration into the UFS community, questioning whether the non-filling of the determiner position before pre-nominal possessives is sensitive to the dialectal factor and integration to the community. Our hypothesis is that the phenomenon presents a dialectal distinction and that the speakers adapt their linguistic behavior, since the number of non-filling will be lower at the end of the course, as an effect of integration into the academic environment and the contact between different varieties. We used the descriptive/inferential method and the theoretical-methodological contribution of Variationist Sociolinguistics (LABOV, 2006; 2008), reconciling with spatial and contact aspects (BRITAIN, 2006; 2008; 2019; CHAMBERS; TRUDGILL, 2004). As corpus, we used the sample Deslocamentos (Displacements) (2019/2020), which has 60 sociolinguistic interviews with the speech of university students from UFS, stratified considering their access to the campus in terms of mobility, time in the course and sex/gender. The results show the predominance of the non-filling of the determiner position before pre-nominal possessives, with 56% (1309/2326). Extralinguistic conditioners demonstrate that the variation is sensitive to the dialect factor and integration over time. The linguistic conditioners have similarities with other researches, mainly regarding the type of phrase, syntactic function and informational status (e.g., SILVA, 1982; 1998a; 1998b; CAMPOS JR.; GUEDES, 2019; SEDRINS et al., 2019; SIQUEIRA, 2020a). We conclude that the variation in the filling of the determiner position in the context of pre-nominal possessives is associated with extralinguistic and linguistic conditioning. The results of this study contribute to the description of Brazilian Portuguese spoken in the state of Sergipe and to the expansion of discussions about the effect of contact over the language.